Optimal scheduling of multi-microgrids with power to hydrogen considering federated demand response - Hu, Qinran; Zhou, Yufeng; Ding, Haohui; Qin, Panhao; Long, Yu (Frontiers in Energy Research, 2022)
Hydrogen is regarded as a promising fuel in the transition to clean energy. Nevertheless, as the demand for hydrogen increases, some microgrids equipped with P2H (MGH) will encounter the issue of primary energy deficiency. Meanwhile, some microgrids (MGs) face the difficulty of being unable to consume surplus energy locally. Hence, we interconnect MGs with different energy characteristics and then establish a collaborative scheduling model of multi-microgrids (MMG). In this model, a federated demand response (FDR) program considering predictive mean voting is designed to coordinate controllable loads of electricity, heat, and hydrogen in different MGs. With the coordination of FDR, the users’ satisfaction and comfort in each MG are kept within an acceptable range. To further adapt to an actual working condition of micro turbine (MT) in MGH, a power interaction method is proposed to maintain the operating power of the MT at optimum load level, shave peak, and shorten the operating periods of MT. The sequence operation theory is applied to deal with the probability density of renewable energy during the solution procedure. A series of case studies on an MMG test system demonstrate the effectiveness of the proposed method.